Advanced Cancer Patients' Prognostic Awareness and Its Association With Anxiety, Depression and Spiritual Well-Being: A Multi-Country Study in Asia. Issue 6 (June 2022) - Ozdemir, S.; Ng, S.; Wong, W.H.M.; Teo, I.; Malhotra, C.; Mathews, J.J.; Joad, A.S.K.; Hapuarachchi, T.; Palat, G.; Tuong, P.N.; Bhatnagar, S.; Ning, X.; et al.
Abstract: Aims: The associations between prognostic awareness, acceptance of illness and psychological outcomes (anxiety, depression and spiritual well-being) remain unclear. This study examined the associations between prognostic awareness and various psychological outcomes and how they can be moderated by patient acceptance of illness (cancer). Materials and methods: In total, 1184 patients with stage IV solid cancer were recruited at major public hospitals across four Asian countries (China, India, Sri Lanka, Vietnam). Prognostic awareness and acceptance of illness were assessed through self-reported understanding of treatment intent and acceptance of illness, respectively. Anxiety and depression were assessed using the Hospital Anxiety and Depression Scale, whereas spiritual well-being was measured using the Functional Assessment of Chronic Illness Therapy – Spiritual Well-Being Scale. Multivariate regressions were used to estimate the associations while controlling for patient characteristics. Results: Compared with being unaware of their prognosis (i.e. believing that their cancer is curable), being aware or unsure of their prognosis was associated with higher anxiety and depressive symptoms, and lower spiritual well-being scores. Acceptance of illness moderated these relationships and improved the psychological outcomes. Conclusions: The results suggest that disclosure of prognostic information should be provided in conjunction with psychological interventions that focus on acceptance of illness. Highlights: Being aware or unsure of prognosis was associated with worse psychological outcomes. Having higher acceptance of illness improved psychological outcomes. Acceptance of illness should be promoted during prognostic discussions.